Rutherford cable made of internal magnesium diffusion MgB2 wires sheathed with Al-Al2O3 particulate metal matrix composite. (5th December 2017) - Kováč, P; Kopera, L; Kováč, J; Hain, M; Melišek, T; Kulich, M; Hušek, I
Abstract: Rutherford MgB2 cable has been made from 12 single-core wires prepared via the internal magnesium diffusion process with a light outer sheath of Al-Al2 O3 particulate metal matrix composite. Initially, critical currents of single-core wires with different diameters (between 1 mm and 0.465 mm) were measured. X-ray tomography was applied for the analysis of the uniformity of a Rutherford cable assembled of 0.465 mm strands. The obtained engineering current density at 4.2 K and 6. 5 T for the present cable (with only 9.6% of MgB2 ) is ∼3.6 times higher in comparison with a similar cable fabricated via the powder-in-tube in situ process with 19.8% of MgB2 phase. The strain tolerance of the cable by bending has shown a critical diameter of 70 mm. AC losses measured via the calibration-free method have shown apparently lower coupling losses for the cabled conductor. The obtained results are promising for future lightweight, mechanically flexible and low AC loss MgB2 superconductors suitable especially for motors or generators.